A perspective of the implications of the common european framework implementation in the colombian socio-cultural context - Ayala Zárate, Jair; Álvarez V., José Aldemar (Colombian Applied Linguistics Journal, 2005)
English language teaching around the world is taking new routes at an accelerated rhythm. As part of a globalized world, Colombia has been trying to accommodate to the new dynamics. One way to do this is through the de-contextualized implementation of standards adapted and/or adopted from overseas. This article aims at promoting refl ection and awareness on implications that might arise due to the implementation of the Common European Framework (CEF) in Colombia. This paper bases its discussion on relevant literature related to bilingualism, the CEF and the Colombian Ministry of Education. The conclusion states the need for the construction of standards regarding foreign language education based on our contextual features, not leaving aside the issue of being globally competent.